MPC Heterogeneity and Household Balance Sheets - Andreas Fagereng; Martin B. Holm; Gisle James Natvik (Center for Economic Studies and ifo Institute (CESifo), 2018)
We use sizeable lottery prizes in Norwegian administrative panel data to characterize households' marginal propensities to consume (MPCs). Our main contribution is to document how MPCs vary with household characteristics and prize size, and how lottery prizes are spent and saved over time. We find that spending spikes in the year of winning, and reverts to normal within 5 years. Controlling for all items on households' balance sheets and characteristics such as education and income, it is the amount won, age and liquid assets that vary systematically with MPCs. Low-liquidity winners of the smallest prizes (around USD 1,500) are estimated to spend all within the year of winning. The same estimate for high-liquidity winners of large prizes (USD 8,300-150,000) is slightly below one half. While the consumption responses we find are high, their systematic relations with observables point toward well-understood mechanisms from existing theory and should be useful to quantify structural models.
Keywords: D12; D14; D91; E21; 330; marginal propensity to consume; household heterogeneity; income shocks